169k views
5 votes
Simplify this expression

Simplify this expression-example-1
User Makaze
by
5.2k points

1 Answer

4 votes

Answer:

option 4

Explanation:

Using the rule of radicals


√(a) ×
√(b) =
√(ab)

Given

(2 - 5
√(6) ) 3
√(2) ← distribute parenthesis by 3
√(2)

= 6
√(2) - 15
√(12)

= 6
√(2) - 15
√(4(3))

= 6
√(2) - 15(
√(4) ×
√(3) )

= 6
√(2) - 15(2
√(3) )

= 6
√(2) - 30
√(3)

User Timothy Jeffcoat
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.